PENGARUH INTEGRATED MARKETING COMMUNICATION TERHADAP BRAND IMAGE (Penelitian Terhadap Busana Muslim Merek Zoya di DKI Jakarta) - Nurianti, Amanda; Suhartati, Suhartati (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to examine and analyze the effect of Integrated Marketing Communication (advertising, sales promotion, personal selling, public relations, direct marketing and internet marketing on the Brand Image "(Research on the Zoya Muslim Clothing Brand in DKI Jakarta)". The type of data used in this research is quantitative data with data collection techniques through questionnaires distributed through Google Forms. The population in this study were consumers of Zoya products in DKI Jakarta. The sampling technique used in this study was convenience random sampling. The number of respondents is 210 respondents . The method of analysis used in this study was multiple linear regression using SEM measuring instruments with the AMOS program. The results showed that advertising, sales promotion, personal selling, public relations have a positive but insignificant effect on the Brand Image, while direct marketing and internet marketing have a positive and significant effect on Brand Image.